2013
DOI: 10.1155/2013/615275
|View full text |Cite
|
Sign up to set email alerts
|

Strain Distribution Measurement of a Shear Panel Damper Developed for Bridge Structure

Abstract: A shear panel damper using low-yield steel is considered as one of cost-effective solutions to reduce earthquake damage to building structure. In this paper, we describe the development of a shear panel damper with high deformation capacity, which is a necessary condition for it to be a bridge bearing. The development is based on the measurement of strain distribution of the shear panels under cyclic loading test. For the measurement, an image processing technique is proposed to use with the two-dimensional fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This system was capable to dissipate the seismic energy through the plastic shear deformation of an external diaphragm steel plate that was welded inside a square hollow section. As mentioned before in this section, a metallic shear panel damper is commonly designed using low-yield-strength steel, owing to its high ductility [88,89]. In this regard, Ming-hasiang et al [61] reported that steel shear plate device with a low yield strength was capable of dissipating or absorbing input energy in a stable behavior.…”
Section: 1 Steel Shear Panel Dampersmentioning
confidence: 99%
“…This system was capable to dissipate the seismic energy through the plastic shear deformation of an external diaphragm steel plate that was welded inside a square hollow section. As mentioned before in this section, a metallic shear panel damper is commonly designed using low-yield-strength steel, owing to its high ductility [88,89]. In this regard, Ming-hasiang et al [61] reported that steel shear plate device with a low yield strength was capable of dissipating or absorbing input energy in a stable behavior.…”
Section: 1 Steel Shear Panel Dampersmentioning
confidence: 99%
“…Other research works have also been conducted to evaluate steel damper behaviour [30][31][32][33][34][35]. A shear panel damper (SPD), which contains a steel plate linked to two upper and lower panels, has also been proposed and investigated by some researchers [36][37][38][39][40][41]. Garivani et al [42] developed a comb-teeth damper (CTD), which comprises steel plates that resemble comb teeth.…”
Section: Introductionmentioning
confidence: 99%
“…These metal dampers generally have a short element length. The simplest metallic damper is a single steel plate, generally welded to the structure, indicated in the literature as a shear panel damper (SPD) [16,17].…”
Section: Introductionmentioning
confidence: 99%